2010
DOI: 10.1115/1.4000570
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Stator Well CFD Studies: Effects of Coolant Supply Geometry on Cavity Sealing Performance

Abstract: The increase of aeroengine performance through the improvement of aerodynamic efficiency of core flow is becoming more and more difficult to achieve. However, there are still some devices that could be improved to enhance global engine efficiency. Particularly, investigations on the internal air cooling systems may lead to a reduction of cooling air with a direct benefit to the overall performance. At the same time, further investigations on heat transfer mechanisms within turbine cavities may help to optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As the number of purge holes decreased, jet momentum increased and the purge flow spread throughout the rim cavity leading to more effective rotor disk cooling. A companion computational fluid dynamics (CFD) study by Andreini et al [12] showed that the cavity flow dynamics differed with purge air delivery angles and purge hole locations. Both the axial and tangential purge flow momentum was shown to affect the cavity sealing effectiveness.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As the number of purge holes decreased, jet momentum increased and the purge flow spread throughout the rim cavity leading to more effective rotor disk cooling. A companion computational fluid dynamics (CFD) study by Andreini et al [12] showed that the cavity flow dynamics differed with purge air delivery angles and purge hole locations. Both the axial and tangential purge flow momentum was shown to affect the cavity sealing effectiveness.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This entrainment phenomenon increased the effectiveness by as much as 50% as a direct result of the purge flow delivery system. Companion numerical studies by Andreini et al [13] showed that increasing the momentum of the purge flow affected the robustness of the purge flow delivery.…”
Section: Introductionmentioning
confidence: 99%
“…There is a two-fold impact: a reduction in bypass losses (therefore increasing useful work) and an increase in cavity swirl, thereby reducing shear stress and windage. Experiments and computations have shown that the location, geometry, and angle of the superposed flows strongly influence the sealing characteristics [6][7][8].…”
Section: Introduction and Review Of Relevant Researchmentioning
confidence: 99%